2011
DOI: 10.1002/wdev.18
|View full text |Cite
|
Sign up to set email alerts
|

Morphogenesis in sea urchin embryos: linking cellular events to gene regulatory network states

Abstract: Gastrulation in the sea urchin begins with ingression of the primary mesenchyme cells (PMCs) at the vegetal pole of the embryo. After entering the blastocoel the PMCs migrate, form a syncitium, and synthesize the skeleton of the embryo. Several hours after the PMCs ingress the vegetal plate buckles to initiate invagination of the archenteron. That morphogenetic process occurs in several steps. The non-skeletogenic cells produce the initial inbending of the vegetal plate. Endoderm cells then rearrange and exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
71
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(71 citation statements)
references
References 96 publications
0
71
0
Order By: Relevance
“…3). This is an important conclusion, which argues against a model in which VEGF signaling is the only or the principle mediator of skeletal patterning in sea urchin embryos, as has been previously suggested (Duloquin et al, 2007;Lyons et al, 2011;Adomako-Ankomah and Ettensohn, 2013;McIntyre et al, 2014). Late VEGFR inhibition (via axitinib) blocks secondary skeletogenesis, which has been interpreted as reflecting a block to biomineralization (Adomako-Ankomah and Ettensohn, 2013).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…3). This is an important conclusion, which argues against a model in which VEGF signaling is the only or the principle mediator of skeletal patterning in sea urchin embryos, as has been previously suggested (Duloquin et al, 2007;Lyons et al, 2011;Adomako-Ankomah and Ettensohn, 2013;McIntyre et al, 2014). Late VEGFR inhibition (via axitinib) blocks secondary skeletogenesis, which has been interpreted as reflecting a block to biomineralization (Adomako-Ankomah and Ettensohn, 2013).…”
Section: Discussionmentioning
confidence: 91%
“…The PMCs are autonomously specified at the posterior pole of the 32-cell stage embryo in a process that is well understood (Logan et al, 1999;Oliveri et al, 2002;Sharma and Ettensohn, 2010). PMCs undergo an epithelial-mesenchymal transition and individually ingress into the blastocoel at the mesenchyme blastula stage (Lyons et al, 2011). The PMCs then migrate into a stereotypic pattern, in which the PMCs are arranged in a vegetal ( posterior) ring around the archenteron, with two ventrolateral clusters (VLCs); slightly later, cords of PMCs extend from the VLCs toward the animal (anterior) pole.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1F). Filopodia extended by the PMCs are likely to be conduits of information between the ectoderm and the PMCs (Miller et al, 1995;Lyons et al, 2012); the abnormal filopodia observed in SB-treated embryos probably reflect a response to abnormal ectodermal patterning information.…”
Section: Results P38 Mapk Inhibition In the Ectoderm Elicits Skeletalmentioning
confidence: 99%
“…Patterning the larval skeleton in sea urchin embryos is a communication-based process in which statically positioned ectodermal cells direct the migration and positioning of primary mesenchymal cells (PMCs), which secrete a calcium carbonate skeleton via biomineralization (Lyons et al, 2012). During gastrulation, the PMCs ingress into the blastocoel, then migrate and organize into a posterior ring around the blastopore, with two ventrolateral clusters from which PMCs migrate anteriorly to form ventrolateral cords.…”
Section: Introductionmentioning
confidence: 99%